Systematic review of Yurchenko vault kinetic and kinematic indicators - Diener, L.; Aedo-Muñoz, E. (Science of Gymnastics Journal, 2019)
The aim of this article was based on determining the most relevant kinematic indicators in the Yurchenko vault technique, using the mechanical purposes of each phase as linking elements. A systematic qualitative review was carried out with an initial search of 67 scientific documents, of which 27 were selected by matching the Yurchenko key words, kinetic, kinematic and artistic gymnastics and their respective combinations. It was concluded that the main kinetic and kinematic indicators involved in this vault are: acceleration, speed, distance, displacement, trajectory, contact time, flight time, percentage of deformation and angular momentum that exert on the center of mass. The following article is proposed as a study instrument to guide in the correct direction of kinetic and kinematic factors to be considered in the effective execution of the Yurchenko vault technique.